Association between Anterior Alveolar Dimensions and Different Vertical Facial Patterns - Abdul Jabbar, Muhammad Nazir, Romesa Khero, Permanand, Muzaffar Qayum Khan Ghouri (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the association of anterior alveolar dimensions with different vertical facial patterns at a tertiary care Hospital. Material and Methods: This Cross-sectional study took place in Orthodontic Department, Institute of Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro, during 6 months form June 2018 to December 2018. Patients with age group 18-30 years and both genders were included. All the subjects were divided into three groups, Average face (Subjects with LAFH-TAFH ratio of 56% -58%), short face (Subjects with LAFH-TAFH ratio of <55%) and long face (Subjects with LAFH-TAFH ratio of >59%), The vertical facial pattern was calculated from TFH i.e., the LAFH and TAFH ratio All the data was recorded by the study proforma for the purpose of analysis. Results: Total 90 patients were studied; their mean age was 21.12+3.47 years. Females were in majority 52.2% and males were 47.8%. Long face was 37.8%, short face 37.8% and average face were 24.4%. Mean upper posterior alveolus width was significantly higher in short face of vertical facial pattern, and mean of upper anterior alveolus height was higher in long face (p-<0.05). Mean of upper anterior alveolus width was significantly higher in average face of vertical facial pattern, and lower anterior alveolus height was markedly higher in long face of vertical facial pattern (p- 0.001). Though mean of lower anterior alveolus width and lower posterior alveolus width were insignificantly associated with vertical facial pattern. Vertical facial pattern was statistically insignificant according to gender p-value 0.226. Conclusion: There was a significant association between dimensions of anterior alveolar among different vertical facial patterns. Kewords: Anterior alveolar dimensions, vertical facial pattern